FM14 Session 2: Communicating Astronomy in our Changing World. Issue Volume 14:Issue A30(2018) (August 2018) - Waller, William H.; Canas, Lina; Agata, Hidehiko; Yamaoka, Hitoshi; Karino, Shigeyuki; Cenadelli, Davide; Bernagozzi, Andrea Ettore; Christille, Jean Marc; Benedetto, Matteo; Calabrese, Matteo; Calcidese, Paolo; Gelderman, Richard; et al.
Abstract: As the IAU heads towards its second century, many changes have simultaneously transformed Astronomy and the human condition world-wide. Amid the amazing recent discoveries of exoplanets, primeval galaxies, and gravitational radiation, the human condition on Earth has become blazingly interconnected, yet beset with ever-increasing problems of over-population, pollution, and never-ending wars. Fossil-fueled global climate change has begun to yield perilous consequences. And the displacement of people from war-torn nations has reached levels not seen since World War II.